Rumen metabolism, meat quality and gene expression changes associated with Nigella sativa L. seeds and Rosmarinus officinalis L. leaf supplementation in Dorper sheep - Jumaah, Kifah Odhaib (2017)
The use of herbs in animal nutrition represents a potent strategy for achieving desired production targets with minimal or no negative impact on animal health and environment. Nonetheless, the impact of herbs on rumen metabolism, growth performance, and product quality is generally less consistent in the published literature. Thus, there is need for additional studies in different production systems to permit tailored decision and informed choices in the utilization of medicinal plants in ruminant nutrition. The current study examined the effects of Nigella sativa (NS) seeds, Rosmarinus officinalis (RO) leaves on in vitro and in vivo rumen metabolism, growth performance, immune response, meat quality and gene expression in Dorper lambs. The study was partitioned into three experiments. The results in present study are illustrated that the effects of different levels of NS seeds and RO leaves on in vitro gas production, rumen fermentation, fatty acids composition and the apparent biohydrogenation of oleic, linoleic and linolenic acids using rumen liquor from Dorper lambs. The NS seeds and RO leaves were supplemented at the rate of 0, 0.5, 1, 1.5 and 2% (w/w) DM of basal substrate [60% forage (urea treated rice straw) and 40% concentrate] and incubated for 24 h at 39°C. Substrates containing RO and NS had greater (P<0.05) gas production than the control substrates. The volume of gas produced increased as the levels of RO and NS increased up to 1.5% and decreased afterwards. Supplementation of RO and NS did not affect (P>0.05) in vitro dry matter digestibility, in vitro organic matter digestibility, rumen pH, CH4 and NH3-N, total volatile fatty acids (VFA) and the molar proportion of acetate, propionate and butyrate. The RO supplements reduced the ruminal concentration of C18:0 and increased the ruminal concentration of C18:1n-9 in a dose dependent manner. The supplementation of RO leaves reduced (P<0.05) the apparent biohydrogenation of C18:1n-9 but had no effect (P>0.05) on the apparent biohydrogenation of C18:2n-6 and C18:3n-3. The results indicated after treatment with Nigella sativa L. seeds, Rosmarinus officinalis L. leaves and their combination on rumen metabolism, nutrient intake and digestibility, growth performance, immune response and blood metabolites in Dorper lambs. Twenty-four entire male Dorper lambs (18.68±0.6 kg, 4-5 months old) were randomly assigned to a concentrate mixture containing on a dry matter basis either, no supplement (control, T1), 1% Rosmarinus officinalis leaves (T2), 1% Nigella sativaseeds (T3), or 1% Rosmarinus officinalis leaves + 1% Nigella sativa seeds (T4). The lambs had ad libitum access to urea-treated rice straw (UTRS) and were raised for 90 days. Supplemented lambs had greater (P<0.05) intake of DM and UTRS than the control lambs. Total and daily weight gain were greater (P< 0.05) in T2 lambs than those fed other diets. The T3 and T4 lambs had greater (P< 0.05) ruminal pH than the T1 and T2 lambs. Supplemented lambs improved ruminal total volatile fatty acids, acetate, propionate and reduced NH3-N, methane gas and C18:0 than the control lambs. Supplemented greater (P< 0.05) serum IgA and IgG compared with the control lambs. On the other hand, there are detectable evident about ameliorative changes of NS seeds, RO leaves and their combination utilized on carcass attributes, gene expression, lipid oxidation and physicochemical properties of LD, ST and SS muscles in Dorper lambs. The results show that the T2 lambs had greater (P< 0.05) slaughter and cold carcass weights than the control lambs. Meat from supplemented lambs had lower (P<0.05) cooking and drip losses, shear force, lightness, and lipid oxidation and greater (P< 0.05) redness compared with the control meat. Postmortem ageing influenced meat quality in Dorper lambs. The impact of dietary supplements on muscle FA varied with muscle type. Furthermore, NS and RO decreased serum total cholesterol, triglycerides, LDL-C and had no effect (P> 0.05) on the expression of SCD and LPL genes in LD and ST muscles in Dorper lambs. The T2 diet up regulated the expression of PRKAA2 gene in LD and ST muscles and up regulated the expression of SREBP1 in LD and ST muscles in Dorper lambs. Overall, our results concluded that Nigella sativa seeds and Rosmarinus officinalis leaves variation in the efficacy of in ruminant nutrition. Dietary supplementation of Nigella sativa seeds and Rosmarinus officinalis leaves had beneficial effects on rumen metabolism, immune response and meat quality in Dorper lambs.